VISUAL ANALYSIS FOR USER MULTIMEDIA INTERACTIONS: APPLYING A VISUAL SOCIAL SEMIOTIC APPROACH - Trisnawati, Suranti (Proceedings of KNASTIK, 2010)
This paper seeks to examine how a visual social semiotics approach can help us to examine user multimedia interactions. As part of the study by the author, this study shows that when interacting with a multimedia text users may make meanings about visual elements they see, whether they are still or moving. This is important to investigate as it may reveal meanings of the visual elements which in turn relate to the effectiveness of the elements. This investigation is important to take into account as interactions between users and visual elements in the context of multimedia environment from a social perspective have rarely been explored. Although visual social semiotics has been used to explore the interaction between viewers and images in the context of printed documents, this approach is appropriate for visual elements in the context of multimedia text. Therefore, visual social semiotic approaches will contribute to discussions regarding the complexity of interactions between the user and the multimedia text.